Degradation of dentin-bonded interfaces treated with collagen cross-linking agents in a cariogenic oral environment: An in situ study. (June 2016) - Hass, Viviane; de Paula, Alexandra Mara; Parreiras, Sibelli; Gutiérrez, Mário Felipe; Luque-Martinez, Issis; de Paris Matos, Thalita; Bandeca, Matheus Coelho; Loguercio, Alessandro D.; Yao, Xiaomei; Wang, Yong; Reis, Alessandra
Abstract: Objectives: To evaluate the effect of treatment using collagen cross-linking agents as primer on resin–dentin bond interfaces subjected to cariogenic oral environment (COE). Methods: Each of forty human teeth had two cavities (4 × 4 × 1.5 mm) prepared within enamel margins. These cavities were acid-etched and treated by the primers containing one of the following treatment agents (6.5% proanthocyanidins, 0.1% riboflavin-UVA activated light, 5% glutaraldehyde or distilled water as a control group). After that the cavities were bonded and restored with resin composite. One restoration for each tooth was tested immediately (IM) and another was included in an intra-oral palatal device that was placed in each mouth of ten adult volunteers for 14 days in COE. After 14 days, the teeth were removed and each restoration was sectioned to obtain a slice for Knoop microhardness (KHN) and resin–dentin bonded sticks for microtensile bond strength (μTBS) and nanoleakage (NL) evaluation. Data were evaluated by two-way ANOVA and Tukey's tests ( α  = 0.05). Results: After 14 days in a COE, the KHN was reduced for all groups, except for the glutaraldehyde group; however, the proanthocyanidins group retained the highest KHN in IM and after COE ( p  < 0.05). The μTBS was not reduced after COE for the proanthocyanidins and glutaraldehyde groups, however only the proanthocyanidins treatment did not increase the NL after COE ( p  > 0.05). Conclusion: The in situ study model seems to be a suitable short-term methodology to investigate the degradation of the bonding interfaces under a more realistic condition. Under COE, the proanthocyanidins and glutaraldehyde treatments produced stable interfaces that are worth further clinical investigation.